2015
DOI: 10.4238/2015.june.26.10
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A and IL-17F polymorphisms and gastric cancer risk: a meta-analysis

Abstract: ABSTRACT. We conducted a meta-analysis of eligible studies to estimate the association between gastric cancer risk and rs2275913G>A IL-17A and rs763780T>C IL-17F polymorphisms. We searched the relevant studies in both Chinese and English through PubMed, the Web of Science, the Cochrane Library, and EMBASE up to January 1, 2014, including 3939 cases and 5407 controls. Seven eligible case-control studies were selected, including seven studies on rs2275913G>A IL-17A and four studies on rs763780T>C IL-17F. The rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Another three case-control studies in Chinese populations reported that the IL-17 rs2275913 A allele was associated with increased risk for the development of gastric cancer (Qinghai et al, 2014;Wang et al, 2014;Hou and Yang, 2015). However, one case-control study and one meta-analysis study reported inconsistent results with the previously mentioned studies (Kutikhin et al, 2014;Li et al, 2015c), and several other studies demonstrated that the IL-17 rs2275913 genetic variation did not affect susceptibility to gastric cancer (Kutikhin et al, 2014;Li et al, 2015c). In the present study, we found that the AA genotype and the A allele of the IL-17 rs2275913 SNP appeared to be associated with a higher risk of developing gastric cancer.…”
Section: Discussioncontrasting
confidence: 35%
“…Another three case-control studies in Chinese populations reported that the IL-17 rs2275913 A allele was associated with increased risk for the development of gastric cancer (Qinghai et al, 2014;Wang et al, 2014;Hou and Yang, 2015). However, one case-control study and one meta-analysis study reported inconsistent results with the previously mentioned studies (Kutikhin et al, 2014;Li et al, 2015c), and several other studies demonstrated that the IL-17 rs2275913 genetic variation did not affect susceptibility to gastric cancer (Kutikhin et al, 2014;Li et al, 2015c). In the present study, we found that the AA genotype and the A allele of the IL-17 rs2275913 SNP appeared to be associated with a higher risk of developing gastric cancer.…”
Section: Discussioncontrasting
confidence: 35%
“…The human IL-17A gene is located on chromosome 6p12.1 [ 34 ]. The a allele of rs2275913 in the promoter region of the IL-17 gene has been reported to be associated with risk of ulcerative colitis [ 35 ], gastric cancer [ 36 ] and atopic dermatitis [ 17 ]. The a allele of rs2275913 enhances IL-17A promoter activity and promotes its transcription, leading to enhanced inflammation in the airway [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much attention has focused on the action of the IL-17/IL-23 axis, which is believed to be a major player in inflammation-related malignancies, such as gastric neoplasms9101112131415162223. Indeed, epidemiological analyses revealed that Asian patients with selected polymorphisms in genes coding for both IL-17 and IL-23 may have an altered risk for developing gastric cancer242526272829. However, very little is known at present about the clinical significance of IL-17 and IL-23 in the pathogenesis of different types of gastric neoplasms in humans.…”
Section: Discussionmentioning
confidence: 99%